The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/1132399
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors among Patients with Positive COVID-19 Test Admitted to ICU

Abstract: Background. Studies that show common characteristics among ICU-admitted patients due to COVID-19 are available on the net, but such studies in Saudi Arabia are limited. Methods. A descriptive cross-sectional study establishing common comorbidities and risk factors among critically ill patients who tested positive for COVID-19 at the National Guard Hospital from March 2, 2020, to March 20, 2021. The data were obtained from the BEST Care System of King Abdulaziz Medical City, computed, and analyzed using SPSS. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[19][20][21] Diabetes is thought to increase the incidence of respiratory illnesses, such as COVID-19, and can have a detrimental effect on the prognosis of patients with respiratory illnesses because chronic inflammation might impair the immune system. [22][23][24] Additionally, older people, who's poorer immunity makes them more susceptible to COVID-19, make up a sizable component of the Mexican population. 25,26 The relationship between COVID-19 and diabetes is a complex one, with both conditions impacting each other in multiple ways as found in many populational studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Diabetes is thought to increase the incidence of respiratory illnesses, such as COVID-19, and can have a detrimental effect on the prognosis of patients with respiratory illnesses because chronic inflammation might impair the immune system. [22][23][24] Additionally, older people, who's poorer immunity makes them more susceptible to COVID-19, make up a sizable component of the Mexican population. 25,26 The relationship between COVID-19 and diabetes is a complex one, with both conditions impacting each other in multiple ways as found in many populational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and hypertension are two comorbidities that are frequently present in diabetes patients and can raise the risk of respiratory problems 19‐21 . Diabetes is thought to increase the incidence of respiratory illnesses, such as COVID‐19, and can have a detrimental effect on the prognosis of patients with respiratory illnesses because chronic inflammation might impair the immune system 22‐24 . Additionally, older people, who's poorer immunity makes them more susceptible to COVID‐19, make up a sizable component of the Mexican population 25,26 …”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%